Social determinants associated with Zika virus infection in pregnant women. - Nivison Nery (Public Library of Science (PLoS), 2021)
This study aims to describe the sociodemographic determinants associated with exposure to Zika Virus (ZIKV) in pregnant women during the 2015-2016 epidemic in Salvador, Brazil. Methods We recruited women who gave birth between October 2015 and January 2016 to a cross-sectional study at a referral maternity hospital in Salvador, Brazil. We collected information on their demographic, socioeconomic, and clinical characteristics, and evaluated their ZIKV exposure using a plaque reduction neutralization test. Logistic regression was then used to assess the relationship between these social determinants and ZIKV exposure status. Results We included 469 pregnant women, of whom 61% had a positive ZIKV result. Multivariate analysis found that lower education (adjusted Prevalence Rate [aPR] 1.21; 95%CI 1.04-1.35) and food insecurity (aPR 1.17; 95%CI 1.01-1.30) were positively associated with ZIKV exposure. Additionally, age was negatively associated with the infection risk (aPR 0.99; 95%CI 0.97-0.998). Conclusion Eve after controlling for age, differences in key social determinants, as education and food security, were associated with the risk of ZIKV infection among pregnant women in Brazil. Our findings elucidate risk factors that can be targeted by future interventions to reduce the impact of ZIKV infection in this vulnerable population.